Vegetarians, fish, poultry, and meat-eaters: who has higher risk of cardiovascular disease incidence and mortality? A prospective study from UK Biobank. (14th December 2020) - Petermann-Rocha, Fanny; Parra-Soto, Solange; Gray, Stuart; Anderson, Jana; Welsh, Paul; Gill, Jason; Sattar, Naveed; Ho, Frederick K; Celis-Morales, Carlos; Pell, Jill P
Abstract: Aims : To compare the incidence and mortality risk for cardiovascular diseases (CVD) [CVD and also ischaemic heart disease (IHD), myocardial infarction (MI), stroke, and heart failure (HF)] among people with different types of diets—including vegetarians, fish eaters, fish and poultry eaters, and meat-eaters—using data from UK Biobank. Methods and results : A total of 422 791 participants (55.4% women) were included in this prospective analysis. Using data from a food frequency questionnaire, four types of diets were derived. Associations between types of diets and health outcomes were investigated using Cox proportional hazard models. Meat-eaters comprised 94.7% of the cohort and were more likely to be obese than other diet groups. After a median follow-up of 8.5 years, fish eaters, compared with meat-eaters, had lower risks of incident CVD hazard ratios (HR): 0.93 [95% confidence intervals (CI): 0.88–0.97], IHD [HR: 0.79 (95% CI: 0.70–0.88)], MI [HR: 0.70 (95% CI: 0.56–0.88)], stroke [HR: 0.79 (95% CI: 0.63–0.98)] and HF [HR: 0.78 (95% CI: 0.63–0.97)], after adjusting for confounders. Vegetarians had lower risk of CVD incidence [HR: 0.91 (95% CI: 0.86–0.96)] relative to meat-eaters. In contrast, the risk of adverse outcomes was not different in fish and poultry eaters compared with meat-eaters. No associations were identified between types of diets and CVD mortality. Conclusion : Eating fish rather than meat or poultry was associated with a lower risk of a range of adverse cardiovascular outcomes. Vegetarianism was only associated with a lower risk of CVD incidence. Graphical Abstract: